Potential of ontology for interoperability in e-government: discussing international initiatives and the brazilian case - Ferneda, Edilson (2016)
Interoperability is one of the fundamental requirements to enable electronic government. Its implementation can be classified into technical, syntactic, semantic, and organizational levels. At the semantic level, ontology is regarded as a practical solution to be considered. In this context, its adoption was identified in several countries, with different levels of maturity and so many focuses as the specific implementations. One of the main challenges to be overcome is the legal question that refers to the legislation to assure “the preservation of the legal meaning of data”. The lack of efficient mechanisms to support the deployment and use of ontologies can turn the overall task time-expensive, restricted in scope, or even unfeasible. Additionally, many initiatives are recent and need to be validated over time. This paper presents a non-exhaustive survey of the state of interoperability in e-government from the perspective of ontologies' use. The cases of Palestine, European Union, Netherlands, Estonia, and Brazil are discussed.